MENELUSURI LOGIKA FIQH MAZHAB HANAFI DALAM PEMBATALAN WUDHU - Robi Hasbullah (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This research is a library research that is motivated by differences of opinion among scholars regarding the law of touching the genitals whether it invalidates wudhu or not. The majority of scholars (jumhur) argue that touching the genitals invalidates wudhu, based on a number of traditions that support this view. However, the Hanafi school is of the opposite opinion, that wudhu is not invalidated by touching the genitals, even if it is done with the palm of the hand and accompanied by lust. This view is based on the assumption that the genitals are no different from other parts of the body, such as the thighs or nose. This study aims to examine more deeply the arguments used by each school of thought and critically analyze the basis of their arguments. The results of the study show that this difference of opinion is based on differences in understanding the hadith and the legal methods used. The findings are expected to provide a more comprehensive understanding in the realm of fiqh as well as a reference for Muslims in determining a more appropriate legal stance in accordance with their conditions and beliefs.